Factories of death Japanese biological warfare 1932-45, and the American cover-up - Harris, Sheldon H. (Routledge, 1994)
Professor Harris's book significantly expands our knowledge of a previously hidden and shameful event of World War Two. Through access to documents unavailable to earlier researchers, he details the activities of Unit 731 of the Imperial Japanese Army, a formation dedicated to conducting bacterial warfare research in Manchuria. Under the command of Colonel Ishii Shiro, the unit conducted innumerable experiments in the 1930s and 1940s. Many involved the use of living subjects, tests that often cost these subjects their lives. Harris addresses the question of whether some of these subjects were Caucasian prisoners of war, and concludes that there is no irrefutable evidence that that was the case. Certainly the vast majority of subjects were Chinese nationals. Harris also shows how the United States government provided immunity from investigation for men who thereby avoided war crimes trials, so that the US could acquire the results of Japanese expertise in bacteriological warfare. This book will be a valuable contribution to our continually enlarging knowledge of human behaviour in wartime.'